Acetylsalicylic acid as an anti-platelet agent: what forms should be used, according to evidence-based medicine? - O. V. Averkov (Кардиоваскулярная терапия и профилактика, 2010)
This analytic paper reviews the evidence on effectiveness, benefits and limitations of one of the best-studied antiplatelet agents – acetylsalicylic acid (ASA). The results of clinical trials, together with so called “gastro-toxicity” of ASA, or Aspirin, and a need for long-term anti-platelet therapy, were the basis for development of various Aspirin forms – soluble, with controlled release, enteric-coated, local (cutaneous), buffer, and combined (Aspirin plus antacids). Currently, the minimal gastro-toxicity has been demonstrated for enteric-coated forms. Specifics of bio-availability, laboratory effects, gastro-intestinal tolerability, and safety could not be the main criteria for choosing a medication form. The choice of an ASA form is defined by the evidence on risk reduction by this form. The extensive evidence on Aspirin as an anti-platelet agent has been obtained in clinical trials using standard ASA. For enteric-coated ASA forms, the evidence on end-point reduction, including mortality reduction, is also available. For other “improved” Aspirin forms, such as buffer, soluble and combined, this evidence is lacking; therefore, their choice could be based only on similarity of laboratory effects and expected lower gastro-toxicity.